2008
DOI: 10.1111/j.1753-6405.2008.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating equations to correct self‐reported height and weight: implications for prevalence of overweight and obesity in Australia

Abstract: Objective: To derive correction equations based on nationally representative data, for the error associated with self‐reported height and weight and to apply these to recent estimates of overweight and obesity in the Australian adult population. Methods: Linear regression was used to derive correction equations to predict reporting error on height, weight and body mass index (BMI) for 8,435 adults, aged 20 and over, who had their height and weight accurately measured as participants of the 1995 National Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 10 publications
10
53
0
1
Order By: Relevance
“…Similarly, corrected height and weight concordance with respective self-reported values also improved, corroborating results of previous studies. 5, 23 Hayes et al, 24 after correcting self-reported weight and height, found that overweight and obesity prevalence CIs estimated from the corrected values were superior to those calculated from selfreported values.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, corrected height and weight concordance with respective self-reported values also improved, corroborating results of previous studies. 5, 23 Hayes et al, 24 after correcting self-reported weight and height, found that overweight and obesity prevalence CIs estimated from the corrected values were superior to those calculated from selfreported values.…”
Section: Discussionmentioning
confidence: 92%
“…Although studies from some countries estimate that self-report is a valid and accurate method, 10,16,17 others consider it unreliable. 1,3,18,19 An assessment of the U.S. population in the National Health and Nutrition Examination Survey (NHANES) II determined that self-reported BMI in Mexican Americans significantly underestimated the true prevalence of overweight and obesity independently of other variables. 4 Our results in South Florida menopausal women show an underestimation of weight and overestimation of height, with no significant differences between Hispanic and nonHispanic women.…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with CATI field tests (Irvine et al 2004). Other studies have shown that self-reported height and weight underestimates BMI (Taylor et al 2006;Hayes et al 2008). It appears that, at least for adults, the perceived height and weight are features that the respondent is consistent about and does not feel any need or desire to check.…”
Section: Discussionmentioning
confidence: 99%